2023
DOI: 10.1057/s41267-022-00594-8
|View full text |Cite
|
Sign up to set email alerts
|

Configuring political relationships to navigate host-country institutional complexity: Insights from Anglophone sub-Saharan Africa

Abstract: We examine how ties with multiple host-country political institutions contribute to MNE subsidiary performance in countries with weak formal institutions. We suggest that forging relationships between subsidiaries and host-country government actors, local chieftains, and religious leaders generates regulative, normative, and cultural-cognitive political resources. We integrate institutional and configuration theories to argue that similarity to an ideal configuration of the three political resources contribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 144 publications
(277 reference statements)
0
2
0
Order By: Relevance
“…From theoretical perspective, the present study furthers scholarly understanding on the dynamics of corporate political activities (Amankwah-Amoah et al, 2022;Boso et al, 2023;de los Reyes & Scholz, 2022;Mellahi et al, 2016) by offering a new understanding of political connectedness and risk-taking using political contributions in monetary terms 13 . In addition, our insights on the PCs and risk-taking illuminates as well as advances our understanding of risk-taking and PCs.…”
Section: Contribution To Theorymentioning
confidence: 78%
See 1 more Smart Citation
“…From theoretical perspective, the present study furthers scholarly understanding on the dynamics of corporate political activities (Amankwah-Amoah et al, 2022;Boso et al, 2023;de los Reyes & Scholz, 2022;Mellahi et al, 2016) by offering a new understanding of political connectedness and risk-taking using political contributions in monetary terms 13 . In addition, our insights on the PCs and risk-taking illuminates as well as advances our understanding of risk-taking and PCs.…”
Section: Contribution To Theorymentioning
confidence: 78%
“…Over the past three decades, scholars have sought to understand the nature and effects of political activities of businesses (Baron, 1995a(Baron, , 1995bBoso et al, 2023;Mellahi et al, 2016). With accumulating body of research in this area, scholars have suggested that by engaging in political activities such as lobbying for preferential regulations and policies, firm can shape the environment to their benefit and curtail risk exposure (Baron et al, 2016;Doh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%